A SYNTACTIC ANALYSIS OF THE ENGLISH DISCOURSE MARKER ONLY AND ITS VIETNAMESE TRANSLATIONAL EQUIVALENTS - Thao, Tran Quoc; Muoi, Nguyen Van (VNU Journal of Foreign Studies; Vol 33 No 3, 2017)
This descriptive and qualitative study, part of a big project, endeavored to explore the syntactic features of the English discourse marker only and its Vietnamese translational equivalents. It involved the development of a bilingual corpus, which consisted of 168 English and 168 Vietnamese instances of sentences containing only . The interpretive contrastive analysis was employed. The findings reveal that only in English often comes in three positions, namely, initial, medial, final, whereas their Vietnamese equivalent usually appears in initial and medial positions. Additionally, there are more similarities than differences in terms of syntactic functions of only used in English and Vietnamese.